Variation of the winter mid-latitude Westerlies in the Northern Hemisphere during the Holocene revealed by aeolian deposits in the southern Tibetan Plateau - Gao, Fuyuan; Yang, Junhuai; Wang, Shuyuan; Wang, Youjun; Li, Kaiming; Wang, Fei; Ling, Zhiyong; Xia, Dunsheng (Quaternary research, 2022)
The mid-latitude Westerlies (MLW) are one of the most important atmospheric circulation systems in the Northern Hemisphere, exerting a huge influence on the climate of the region downwind, and thus on vegetation, water resources, and human wellbeing. However, the seasonal variation of the MLW during the Holocene is not yet been fully understood, especially when its contribution is the most important. Here, we used end-member (EM) modeling analysis of the grain-size distributions of a high-altitude aeolian sedimentary sequence (4452 m a.s.l.) from the Yarlung Zangbo River valley in the southern Tibetan Plateau to reveal variations in the winter MLW during the Holocene. Analysis of seasonal differences in modern atmospheric circulation suggests that the southern Tibetan Plateau was heavily influenced by the mid-latitude Westerlies at the 400, 500, and 600 hPa levels in winter, while it was seldom influenced at these levels in summer. Four grain-size end-members are identified, representing distinct aerodynamic environments, of which EM1 (modal grain size 8.1 μm) can be used as a proxy of the winter MLW. A reconstruction of the variation of the winter MLW during the Holocene based on EM1 revealed that a weaker winter MLW occurred during the Early to Middle Holocene, and a stronger winter MLW during the Middle to Late Holocene. Overall, we suggest that this change in the winter MLW was closely related to the insolation/temperature/pressure gradient between low and high latitudes in the Northern Hemisphere.